2020
DOI: 10.1111/plb.13177
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal size, ploidy and polyembryony in Eriotheca Stellate Trichome Species Complex (Bombacoideae – Malvaceae) in the Cerrados of Brazil

Abstract: • Geographic parthenogenesis, range expansion of apomictic plants after climate changes, has been described for Northern Hemisphere gametophytic apomicts. But similar trends have been observed for sporophytic apomicts of Cerrado, the savannas in Brazil. Eriotheca pubescens is a common Cerrado tree, an agamic complex of either hexaploid/polyembryonic apomicts or tetraploid/monoembryonic sexual individuals. Some populations have been described as a new species, Eriotheca estevesiae, all included in the Eriotheca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 38 publications
(144 reference statements)
1
26
0
Order By: Relevance
“…Only one seedling actually developed and although the number of hybridization pollinations prevents making generalizations and the early death of the putative hybrid seedling made impossible further ploidy assessment via flow cytometry, stomatal morphometrics suggested an intermediate ploidy level. Stomatal morphometry stomatal was consistent with ploidy level in Eriotheca (Marinho et al 2014a(Marinho et al , 2020. The Nested ANOVA analyzes showed that the species cytotypes (and pooled ploidy levels) were the most important factors explaining stomatal size variation, possibly because polyploidization affects cell size of Eriotheca, as it does in Citrus (Costa et al 2004), Musa (Vandenhout et al 1995) and other groups (Balao et al 2011).…”
Section: Stomata and Genome Size Measurementsmentioning
confidence: 69%
See 4 more Smart Citations
“…Only one seedling actually developed and although the number of hybridization pollinations prevents making generalizations and the early death of the putative hybrid seedling made impossible further ploidy assessment via flow cytometry, stomatal morphometrics suggested an intermediate ploidy level. Stomatal morphometry stomatal was consistent with ploidy level in Eriotheca (Marinho et al 2014a(Marinho et al , 2020. The Nested ANOVA analyzes showed that the species cytotypes (and pooled ploidy levels) were the most important factors explaining stomatal size variation, possibly because polyploidization affects cell size of Eriotheca, as it does in Citrus (Costa et al 2004), Musa (Vandenhout et al 1995) and other groups (Balao et al 2011).…”
Section: Stomata and Genome Size Measurementsmentioning
confidence: 69%
“…Some cytotypes of E. gracilipes and E. pubescens occur sympatrically in the Triângulo Mineiro region and both sexual and apomictic individuals require pollination to set fruits and viable seeds (Mendes-Rodrigues et al 2019). As mentioned before, pollen and stomatal sizes are clearly correlated to ploidy levels in the three Eriotheca species (Marinho et al 2014a(Marinho et al , 2020Mendes-Rodrigues et al 2019).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations